2013
DOI: 10.1089/aid.2012.0096
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Abnormalities and Associated Factors in a Cohort of Asymptomatic HIV-Infected Patients

Abstract: HIV patients have been reported to have a greater prevalence of echocardiographic abnormalities. We aimed to determine the prevalence of these abnormalities and their associated factors. This was an observational study of a cohort of asymptomatic HIV patients. Data were recorded on factors of cardiovascular interest and those related to HIV infection. All the subjects underwent a transthoracic echocardiogram. The study included 196 patients, 85.2% men, mean age 46.4 years, with a mean duration of HIV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
2
24
1
1
Order By: Relevance
“…One clue supporting the latter possibility has come from follow-up studies that further dissected the regimen, in which specific presentation of the MPER peptide in liposomes i.e. in an orientation similar to that in the HIV-1 virion (in contrast to general multimeric display), and only with MPLA (versus other TLR agonists tested), were both key to induce optimal serum bnAb IgG titers in 2F5 and 4E10 VDJ+VJ mice ((107); H. Verville, L. Verkoczy et al, manuscript in preparation), suggesting a key role for lipid components in overcoming anergy of MPER + bnAbs. An intriguing remaining question regarding overcoming MPER bnAb anergy is whether strength of T H priming and degree of tolerization are related (i.e.…”
Section: Formal Demonstration Of Bnab Tolerance Controls Using Human mentioning
confidence: 99%
“…One clue supporting the latter possibility has come from follow-up studies that further dissected the regimen, in which specific presentation of the MPER peptide in liposomes i.e. in an orientation similar to that in the HIV-1 virion (in contrast to general multimeric display), and only with MPLA (versus other TLR agonists tested), were both key to induce optimal serum bnAb IgG titers in 2F5 and 4E10 VDJ+VJ mice ((107); H. Verville, L. Verkoczy et al, manuscript in preparation), suggesting a key role for lipid components in overcoming anergy of MPER + bnAbs. An intriguing remaining question regarding overcoming MPER bnAb anergy is whether strength of T H priming and degree of tolerization are related (i.e.…”
Section: Formal Demonstration Of Bnab Tolerance Controls Using Human mentioning
confidence: 99%
“…Levels of T-cell activation and innate system activation are often higher than that observed in well-matched uninfected adults (5,6). These persistent abnormalities may contribute to abnormal vaccine responses (7,8), a higher than normal incidence of non-AIDS-related cancers (9,10) and increased risk for clinical conditions associated with chronic inflammation (e.g., cardiac disease, clotting disorders, pulmonary hypertension, emphysema, and stroke) (11)(12)(13)(14)(15)(16)(17)(18). Thus, improvements over current approaches to treatment of HIV infection that more fully restore normal immune function might significantly improve health and life expectancy.…”
mentioning
confidence: 99%
“…They also mentioned that the prevalence of HIV-related PAH is underestimated since clinical studies tend to include symptomatic patients. Isasti et al confirmed the notion regarding underestimation of the prevalence of PH in a study of 196 HIV-infected individuals who lacked respiratory or cardiac complaints [24, 25]. It was demonstrated that 2.6% of patients did have evidence of PH and 6.1% had right ventricular systolic dysfunction based on echocardiography.…”
Section: Epidemiology Of Pulmonary Hypertension In Patients With Hmentioning
confidence: 86%